2017
DOI: 10.1002/cbic.201600594
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme from an Uncultivated Sponge Bacterium Catalyzes S‐Methylation in a Ribosomal Peptide

Abstract: Amino acid modifications are essential for the structural diversity and bioactivity of ribosomally synthesized and post-translationally modified peptide natural products (RiPPs). A particularly large and virtually untapped pool of unusual RiPPs and associated modifying enzymes is provided by uncultivated bacteria. An example is the chemically rich sponge symbiont "Candidatus Entotheonella factor", which produces the hypermodified polytheonamides of the poorly studied proteusin RiPP family. In addition to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…E. factor and Ca. E. gemina in T. swinhoei Y revealed a large diversity of additional biosynthetic gene clusters, of which at least one is functional (16,24). Entotheonella filaments were also previously described from the discodermolide-containing sponge Discodermia dissoluta (44) and a swinholide-and theopalauamide-containing Palauan chemotype of T. swinhoei (13).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…E. factor and Ca. E. gemina in T. swinhoei Y revealed a large diversity of additional biosynthetic gene clusters, of which at least one is functional (16,24). Entotheonella filaments were also previously described from the discodermolide-containing sponge Discodermia dissoluta (44) and a swinholide-and theopalauamide-containing Palauan chemotype of T. swinhoei (13).…”
Section: Discussionmentioning
confidence: 80%
“…By genomic and biosynthetic studies of T. swinhoei Y (14-17), a Japanese variant from Hachijo Island with a yellow interior, we and collaborators recently identified the source of onnamide-/ theopederin-type polyketides (18), the ribosomal peptides polytheonamides (3), and the nonribosomal peptides keramamide/orbiculamide (19,20), cyclotheonamide (21), and nazumamide (22). All of these compounds were linked to a single producer, "Candidatus Entotheonella factor" (16,23,24). This remarkable filamentous bacterium contains many additional biosynthetic gene clusters (BGCs) of as-yet unknown function, and is accompanied in the sponge by a second BGC-rich phylotype, "Ca.…”
mentioning
confidence: 99%
“…'Entotheonella factor', the uncultivated sponge symbiont that is the source of the polytheonamides (see Section 3.12), contains in its genome a second proteusin-type BGC (pty locus). 369 Coexpression studies using precursor peptide-maturase gene combinations and E. coli as host revealed that PtyS, a SAM-dependent methyltransferase, catalyzes S-methylation of up to four Cys residues as the modication type. 369 Prior to these studies, S-methylation was known in non-ribosomal peptide biosynthesis but not for RiPPs.…”
Section: Nosl Rearrangement During Nosiheptide Biosynthesismentioning
confidence: 99%
“…T. swinhoei comprises several sponge variants with diverse and mostly nonoverlapping sets of bioactive metabolites (11). In each of the Japanese chemotypes T. swinhoei Y and W, a single symbiont ["Candidatus Entotheonella factor" (10,12,13) or "Candidatus Entotheonella serta" (14), respectively] produces all or almost all of the polyketide and peptide natural products known from the sponges. Each symbiont harbors diverse and almost orthogonal sets of biosynthetic gene clusters (BGCs), providing a rationale for the distinct chemistry of T. swinhoei variants.…”
mentioning
confidence: 99%